Anatomical characteristics of the styloid process in cerebral infarction related to carotid artery dissection: a case-control study - Shi, Shuna; Wang, Limei; Luo, Haiyang; Fu, Zhenling; Liu, Yutao (Frontiers in Neurology, 2025)
PurposeTo verify the hypothesis that length and inclination angle of the styloid process may lead to cerebral infarction related to carotid artery dissection through comparison of the length and inclination angle of the styloid process in middle-aged and young stroke patients undergoing carotid artery dissection, vertebral artery dissection, and non-dissection controls.MethodsThis was a Retrospective, single-center, case-control study that enrolled patients with cerebral infarction related to internal carotid artery dissection, vertebral artery dissection, and non-dissection controls. Eighteen patients with carotid artery dissection patients (cases) were compared with 34 sex-matched patients with vertebral artery dissection (G1) and 55 sex-matched patients without dissection (G2). The length and inclination angle of the styloid process were measured using Computed tomography angiography images. Differences between groups were estimated using the Student's t-test.ResultsStyloid process length ipsilateral to the carotid artery dissection was not significantly longer than that of the contralateral side of the cases (p > 0.05), or to those of the ipsilateral and contralateral sides in patients with vertebral artery dissection (p > 0.05). The styloid process length ipsilateral to the dissection was significantly longer than those of the left and right sides of control patients (p < 0.05 for both), while the inclination angle of the cases was significantly larger than those of the ipsilateral and contralateral sides of the vertebral artery dissection patients (p < 0.05), and to the left and right sides of control patients (both p < 0.05).ConclusionLong styloid process length and a large inclination angle appear to be risk factors for carotid artery dissection (CAD).